Geneologi Gerakan Pembaruan Islam - Saripuddin, Yulia; Az Zahra, Urmila; Amin, M. (PT Maju Malaqbi Makkarana, 2026)
This article examines the genealogy of Islamic reform movements through a historical and qualitative approach. Islamic reform emerged as a response to Western colonialism, internal intellectual decline within Muslim societies, and the challenges of modernity. By tracing the ideas of key reformist figures such as Jamal al-Din al-Afghani and Muhammad Abduh, this study demonstrates that Islamic reform is a dynamic and adaptive process grounded in ijtihad, rational thought, and social reform. The findings indicate that Islamic reform movements have contributed significantly to the development of religious moderation, the modernization of Islamic education, and efforts to counter religious radicalism in contemporary contexts. Therefore, Islamic reform represents a continuous tradition within Islam that seeks to harmonize religious values with changing social realities without compromising core Islamic principles.